Thermoplastic elastomer composition and its use

By cross-linking ethylene α-olefin non-conjugated polyene copolymer (EPDM) with a softener in thermoplastic elastomer compositions, the challenges of achieving both formability and flame retardancy are addressed, resulting in a composition with improved moldability and flame retardancy.

JP7657088B2Active Publication Date: 2025-04-04MITSUI CHEMICALS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021058430
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-04-04
Estimated Expiration
2041-03-30

AI Technical Summary

Technical Problem

Conventional thermoplastic elastomer compositions face challenges in achieving both formability and flame retardancy, as high softener content improves moldability but decreases flame retardancy, while high flame retardant content deteriorates fluidity and moldability.

Method used

The composition incorporates ethylene α-olefin non-conjugated polyene copolymer (EPDM) to cross-link at least part of the mixture, incorporating a softener and suppressing its volatilization, thereby enhancing flame retardancy and allowing for increased softener content for improved moldability.

Benefits of technology

This approach results in a thermoplastic elastomer composition that balances formability and flame retardancy, offering excellent moldability and enhanced flame retardancy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657088000001
    Figure 0007657088000001
Patent Text Reader

Abstract

To provide a thermoplastic elastomer composition which achieves both moldability and flame retardancy.SOLUTION: The thermoplastic elastomer composition contains 100 pts.mass of a propylene-based polymer (A), 10-300 pts.mass of an ethylene / α-olefin / nonconjugated polyene copolymer (B), 30-250 pts.mass of a hydrogenated product (C) of a block copolymer having a block mainly composed of a conjugated diene monomer unit and a block mainly composed of a vinyl aromatic monomer unit, 100-300 pts.mass of a softener (D), and 1-30 pts.mass of a polyorganosiloxane (E) and is at least partially crosslinked.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic elastomer composition and its use. [Background technology]

[0002] Soft polyvinyl chloride resins have traditionally been used primarily for interior skin materials such as instrument panels and door trims in automobiles, but in recent years, olefin-based thermoplastic elastomers have begun to be used in order to reduce the weight of materials.

[0003] As such an olefin-based thermoplastic elastomer, for example, Patent Document 1 discloses a thermoplastic elastomer composition containing (A) 100 parts by mass of a polypropylene-based resin, (B) 80 to 200 parts by mass of a hydrogenated block copolymer having at least one block mainly composed of conjugated diene monomer units and at least one block mainly composed of vinyl aromatic monomer units, (C) 100 to 250 parts by mass of a softener, and (D) 5 to 20 parts by mass of a polyorganosiloxane.

[0004] When manufacturing interior skins from raw skin material in which the above-mentioned olefin thermoplastic elastomer is processed into a sheet shape, the elastomer is integrated with aggregates by vacuum forming, injection press molding, lamination, etc. However, whichever method is used, the manufacturing process becomes long, which causes the cost of the part to increase.

[0005] One possible molding method that can keep costs down is to mold the base material by injection molding, then move the mold to form a gap between the surface of the base material and the mold face, and then injection mold the skin material into the gap. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2011 / 155571 Summary of the Invention [Problem to be solved by the invention]

[0007] When injecting a thermoplastic elastomer composition, a large amount of softener is often added to improve fluidity (moldability), but the inclusion of a large amount of softener tends to decrease flame retardancy. On the other hand, the inclusion of a large amount of flame retardant tends to deteriorate the fluidity and decrease moldability. With conventional thermoplastic elastomer compositions such as those described in Patent Document 1, it was difficult to achieve both moldability and flame retardancy.

[0008] An object of the present invention is to provide a thermoplastic elastomer composition which combines moldability and flame retardancy. [Means for solving the problem]

[0009] The present inventors have conducted extensive research to solve the above problems, and as a result have found that by blending an ethylene-α-olefin-non-conjugated polyene copolymer (EPDM) with a thermoplastic elastomer composition and at least partially crosslinking it, the crosslinked body incorporates a softener and suppresses its volatilization, thereby improving flame retardancy and enabling a large amount of softener to be incorporated, resulting in excellent moldability, which has led to the completion of the present invention.

[0010] That is, the thermoplastic elastomer composition of the present invention comprises 100 parts by mass of a propylene-based polymer (A), 10 to 300 parts by mass of an ethylene-α-olefin-non-conjugated polyene copolymer (B), 30 to 250 parts by mass of a hydrogenated block copolymer (C) having a block mainly composed of conjugated diene monomer units and a block mainly composed of vinyl aromatic monomer units, 100 to 300 parts by mass of a softener (D), and 1 to 30 parts by mass of a polyorganosiloxane (E), and is characterized in that it is at least partially crosslinked. Effect of the Invention

[0011] According to the present invention, it is possible to provide a thermoplastic elastomer composition that combines moldability and flame retardancy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. [Thermoplastic elastomer composition] The thermoplastic elastomer composition of the present invention (hereinafter also simply referred to as "the composition of the present invention") comprises 100 parts by mass of a propylene-based polymer (A), 10 to 300 parts by mass of an ethylene-α-olefin-non-conjugated polyene copolymer (B), 30 to 250 parts by mass of a hydrogenated block copolymer having a block mainly composed of conjugated diene monomer units and a block mainly composed of vinyl aromatic monomer units (C), 100 to 300 parts by mass of a softener (D), and 1 to 30 parts by mass of a polyorganosiloxane (E), and is characterized in that it is at least partially crosslinked.

[0013] The crosslinking is preferably caused by an organic peroxide (F). The composition of the present invention may further contain an ethylene-α-olefin copolymer (G) containing ethylene units and α-olefin units having 3 to 20 carbon atoms in an amount of more than 0 part by mass and not more than 300 parts by mass.

[0014] Each component contained in the composition of the present invention will be described below.

[0015] <Propylene-based polymer (A)> Component (A) is not particularly limited as long as it is a polymer containing propylene as the main monomer, and examples thereof include isotactic polypropylene, which is a homopolymer; isotactic copolymers (including block copolymers and random copolymers) of propylene and other α-olefins such as ethylene, 1-butene, 1-pentene, 1-hexene, etc. Among these, homopolypropylene is preferred.

[0016] The melt flow rate of component (A) is preferably in the range of 0.1 to 100 g / 10 min (230° C., 2.16 kg load (0.212 MPa)). By making the melt flow rate 100 g / 10 min or less, the heat resistance and mechanical strength of the thermoplastic elastomer composition can be further improved, and by making it 0.1 g / 10 min or more, the flowability and moldability can be further improved.

[0017] Component (A) can be produced by a known method, and a commercially available product may also be used as component (A).

[0018] <Ethylene-α-olefin-non-conjugated polyene copolymer (B)> Component (B) is an ethylene-α-olefin-non-conjugated polyene copolymer containing a structural unit (b1) derived from ethylene, a structural unit (b2) derived from an α-olefin having 3 to 20 carbon atoms, and a structural unit (b3) derived from a non-conjugated polyene. Component (B) may be used alone or in combination of two or more types.

[0019] The molar ratio (b1) / (b2) of the structural unit (b1) and the structural unit (b2) in the component (B) is preferably 50 / 50 to 95 / 5, more preferably 60 / 40 to 80 / 20, and even more preferably 65 / 35 to 75 / 25.

[0020] On the other hand, the specific amount of the structural unit (b3) derived from a non-conjugated polyene in component (B) is preferably 2 to 20 mass % relative to the total amount of component (B).

[0021] Specific examples of the α-olefin having 3 to 20 carbon atoms constituting component (B) include propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-nonadecene, 1-eicosene, 9-methyl-1-decene, 11-methyl-1-dodecene, 12-ethyl-1-tetradecene, and the like.

[0022] Among them, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene are included. The component (B) may contain only one type of the structural unit (b2) derived from an α-olefin, or may contain two or more types.

[0023] The non-conjugated polyene constituting component (B) may be any compound that does not have a conjugated structure and has two or more carbon-carbon double bonds. Specific examples thereof include linear non-conjugated dienes such as 1,4-hexadiene, 3-methyl-1,4-hexadiene, 4-methyl-1,4-hexadiene, 5-methyl-1,4-hexadiene, 4,5-dimethyl-1,4-hexadiene, 7-methyl-1,6-octadiene, 8-methyl-4-ethylidene-1,7-nonadiene, and 4-ethylidene-1,7-undecadiene; methyltetrahydroindene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, 5-biphenyl-2-phenylene, 5-isopropylidene-2-norbornene, and 5-bis(2-phenylene)-2-phenylene; Cyclic non-conjugated dienes such as 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, 2-propenyl-2,2-norbornadiene, and 4-ethylidene-8-methyl-1,7-norbornene are included.

[0024] Among these non-conjugated polyenes, 5-ethylidene-2-norbornene (ENB) and 5-vinyl-2-norbornene (VNB) are particularly preferred. Component (B) may contain only one type of structural unit (b3) derived from a non-conjugated polyene, or may contain two or more types.

[0025] It is preferable that at least a part of the component (B) is crosslinked. This allows the crosslinked body to incorporate the softener and suppress the volatilization of the softener, thereby improving the flame retardancy and allowing a large amount of the softener to be contained, resulting in a composition with excellent moldability. It is preferable that the crosslinking of the component (B) is caused by an organic peroxide (F) described later.

[0026] Component (B) can be produced by a conventionally known method. Component (B) may be a so-called oil-extended rubber, in which a softener, preferably a mineral oil-based softener, is blended during its production. The mineral oil-based softener may be a conventionally known mineral oil-based softener, examples of which include paraffin-based process oil. The softener blended in component (B) may be the same as softener (D) described below, or may be different.

[0027] The content of component (B) in the composition of the present invention is 10 to 300 parts by mass, preferably 15 to 200 parts by mass, more preferably 20 to 100 parts by mass, and further preferably 25 to 80 parts by mass, relative to 100 parts by mass of component (A). By having the content of component (B) within the above range, volatilization of the softener is suppressed, and flame retardancy can be improved.

[0028] <Hydrogenated block copolymer (C)> Component (C) is a hydrogenated (also called hydrogenated) block copolymer having at least one block mainly composed of a conjugated diene monomer unit and at least one block mainly composed of a vinyl aromatic monomer unit. Here, the term "vinyl aromatic monomer unit" refers to a structural unit of a polymer resulting from polymerization of a vinyl aromatic compound monomer, and the structure is a molecular structure in which two carbon atoms of a substituted ethylene group derived from a substituted vinyl group are bonded to each other. The term "conjugated diene monomer unit" refers to a structural unit of a polymer resulting from polymerization of a conjugated diene monomer, and the structure is a molecular structure in which two carbon atoms of an olefin derived from a conjugated diene monomer are bonded to each other. In the block copolymer, "mainly composed" means that the copolymer block contains a monomer unit derived from a conjugated diene monomer (or a vinyl aromatic monomer) in an amount of preferably 50% by mass or more, more preferably 55% by mass or more, even more preferably 60% by mass or more, and particularly preferably 70% by mass or more. For example, a block mainly composed of conjugated diene monomer units means that the block contains monomer units derived from conjugated diene monomers in an amount of preferably 50% by mass or more, more preferably 55% by mass or more, even more preferably 60% by mass or more, and particularly preferably 65% ​​by mass or more.

[0029] In the present embodiment, the vinyl aromatic monomer is not particularly limited, and examples thereof include vinyl aromatic compounds such as styrene, α-methylstyrene, p-methylstyrene, divinylbenzene, 1,1-diphenylethylene, N,N-dimethyl-p-aminoethylstyrene, and N,N-diethyl-p-aminoethylstyrene. These may be used alone or in combination of two or more. Among these, styrene is preferred from the viewpoint of economic efficiency.

[0030] In this embodiment, the conjugated diene monomer is a diolefin having a pair of conjugated double bonds, and examples thereof include 1,3-butadiene (butadiene), 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, and 1,3-hexadiene. Among these, butadiene and isoprene are preferred from the viewpoint of economic efficiency. These may be used alone or in combination of two or more.

[0031] The arrangement of each block in the hydrogenated block copolymer of the present embodiment is not particularly limited, and any suitable arrangement may be adopted. For example, when a polymer block consisting of an aromatic vinyl monomer unit is represented by S, and a polymer block consisting of a conjugated diene monomer unit and / or a partially hydrogenated unit thereof is represented by B, the hydrogenated block copolymer has the arrangement of SB,S(BS). n1 (wherein n1 represents an integer of 1 to 3), S(BSB) n2 (wherein n2 represents an integer of 1 to 2), and linear block copolymers represented by (SB) n3 X (wherein n3 is an integer of 3 to 6, and X is a coupling agent residue such as silicon tetrachloride, tin tetrachloride, or a polyepoxy compound). Among these, linear block copolymers of SB type 2 (diblock), SBS type 3 (triblock), and SBSB type 4 (tetrablock) are preferred.

[0032] The content of the vinyl aromatic monomer unit in component (C) is preferably 30 to 80 mass%, more preferably 35 to 75 mass%, and particularly preferably 40 to 70 mass%, from the viewpoint of heat resistance and dispersibility. By making the content of the vinyl aromatic monomer unit 30 mass% or more, the mechanical properties can be further improved, and by making it 80 mass% or less, the low temperature properties can be further improved. The content of the vinyl aromatic monomer unit in component (C) can be measured by nuclear magnetic resonance spectrum analysis (NMR).

[0033] From the viewpoint of mechanical strength, the content of the vinyl aromatic monomer unit block in component (C) is preferably 10% by mass or more, more preferably 10 to 40% by mass. Here, the content of the vinyl aromatic compound polymer block in component (C) is defined by the following formula using the mass of the vinyl aromatic compound polymer block (here, vinyl aromatic compound polymers having an average degree of polymerization of about 30 or less are excluded) obtained by a method of oxidatively decomposing a copolymer before hydrogenation with tert-butyl hydroperoxide using osmium tetroxide as a catalyst (the method described in IM Kolthoff, et al., J. Polym. Sci. 1, 429 (1946), hereinafter also referred to as the "osmium tetroxide decomposition method").

[0034] Content of vinyl aromatic compound polymer block (mass%)=(mass of vinyl aromatic compound polymer block in copolymer before hydrogenation / mass of copolymer before hydrogenation)×100

[0035] When a plurality of polymer blocks are present in component (C), the molecular weight, composition, and other structures of the polymer blocks may be the same or different. For example, component (C) may include a hydrogenated copolymer block containing a conjugated diene monomer unit and a vinyl aromatic monomer unit, and a hydrogenated copolymer block mainly composed of a conjugated diene monomer unit. The boundaries and ends of the blocks do not necessarily need to be clearly distinguished. The distribution of the vinyl aromatic monomer units in each polymer block is not particularly limited, and may be uniform, tapered, stepped, convex, or concave. In addition, a crystalline portion may be present in the polymer block.

[0036] The mode of distribution of vinyl units of the conjugated diene monomer units in each polymer block is not particularly limited, and for example, the distribution may be biased. Methods for controlling the distribution of vinyl units include a method of adding a vinylizing agent during polymerization and a method of changing the polymerization temperature. In addition, the distribution of the hydrogenation rate of the conjugated diene monomer units may be biased. The distribution of the hydrogenation rate can be controlled by a method of changing the distribution state of vinyl units, a method of copolymerizing isoprene and butadiene and then hydrogenating them using a hydrogenation catalyst described later, and utilizing the difference in hydrogenation rate between the isoprene unit and the butadiene unit, and the like.

[0037] From the viewpoints of heat resistance, aging resistance and weather resistance, component (C) has preferably 75 mol % or more, more preferably 85 mol % or more, and even more preferably 97 mol % or more of the unsaturated bonds contained in the conjugated diene monomer units before hydrogenation hydrogenated.

[0038] The hydrogenation catalyst used for hydrogenation is not particularly limited, and may be any of the conventionally known homogeneous hydrogenation catalysts, such as (1) supported heterogeneous hydrogenation catalysts in which metals such as Ni, Pt, Pd, Ru, etc. are supported on carbon, silica, alumina, diatomaceous earth, etc., (2) so-called Ziegler-type hydrogenation catalysts in which transition metal salts such as organic acid salts or acetylacetone salts of Ni, Co, Fe, Cr, etc. are used with reducing agents such as organoaluminum, and (3) so-called organometallic complexes of organometallic compounds of Ti, Ru, Rh, Zr, etc. Specific examples of the hydrogenation catalyst include the hydrogenation catalysts described in JP-B-42-008704, JP-B-43-006636, JP-B-63-004841, JP-B-01-037970, JP-B-01-053851, JP-B-02-009041, etc. Among these, preferred hydrogenation catalysts include reducing organometallic compounds such as titanocene compounds.

[0039] As the titanocene compound, for example, the compounds described in JP-A-08-109219 can be used. Specific examples include compounds having at least one ligand having a (substituted) cyclopentadienyl skeleton, an indenyl skeleton or a fluorenyl skeleton, such as biscyclopentadienyltitanium dichloride and monopentamethylcyclopentadienyltitanium trichloride.

[0040] Examples of the reducing organometallic compound include organoalkali metal compounds such as organolithium compounds, organomagnesium compounds, organoaluminum compounds, organoboron compounds, and organozinc compounds.

[0041] In this embodiment, the polymerization method of the component (C) before hydrogenation is not particularly limited, and a known method can be adopted, for example, the methods described in JP-B-36-019286, JP-B-43-017979, JP-B-46-032415, JP-B-49-036957, JP-B-48-002423, JP-B-48-004106, JP-B-56-028925, JP-A-59-166518, JP-A-60-186577, etc. can be mentioned.

[0042] If necessary, the component (C) may have a polar group. Examples of the polar group include a hydroxyl group, a carboxyl group, a carbonyl group, a thiocarbonyl group, an acid halide group, an acid anhydride group, a thiocarboxylic acid group, an aldehyde group, a thioaldehyde group, a carboxylate group, an amide group, a sulfonic acid group, a sulfonate group, a phosphoric acid group, a phosphoric acid ester group, an amino group, an imino group, a nitrile group, a pyridyl group, a quinoline group, an epoxy group, a thioepoxy group, a sulfide group, an isocyanate group, an isothiocyanate group, a silicon halide group, an alkoxy silicon group, a tin halide group, a boronic acid group, a boron-containing group, a boronate salt group, an alkoxy tin group, and a phenyl tin group.

[0043] The vinyl bond content in the conjugated diene monomer unit in the pre-hydrogenated copolymer in component (C) is preferably 5 mol% or more from the viewpoints of flexibility and scratch resistance, and is preferably 70 mol% or less from the viewpoints of productivity, elongation at break and scratch resistance. The vinyl bond content in the conjugated diene monomer unit is more preferably 10 to 50 mol%, further preferably 10 to 30 mol%, particularly preferably 10 to 25 mol%.

[0044] The vinyl bond content herein means the ratio of 1,2-bonds and 3,4-bonds to the 1,2-bonds, 3,4-bonds and 1,4-bonds incorporated in the conjugated diene before hydrogenation. The vinyl bond content can be measured by NMR.

[0045] The weight average molecular weight of the component (C) before crosslinking is not particularly limited, but is preferably 50,000 or more from the viewpoint of scratch resistance, and is preferably 400,000 or less from the viewpoint of molding flowability, and more preferably 50,000 to 300,000. The molecular weight distribution (Mw / Mn: weight average molecular weight / number average molecular weight) is not particularly limited, but is preferably a value close to 1 from the viewpoint of scratch resistance. The weight average molecular weight and number average molecular weight can be determined by gel permeation chromatography (GPC; Shimadzu Corporation, device name "LC-10") using tetrahydrofuran (1.0 mL / min) as a solvent, at an oven temperature of 40°C, and columns: TSKgelGMHXL (4.6 mmID x 30 cm, 2 columns). The weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) are calculated as polystyrene-equivalent molecular weights.

[0046] From the viewpoint of scratch resistance, the component (C) preferably contains a hydrogenated product of a block copolymer that mainly contains conjugated diene monomer units and has a copolymer block containing vinyl aromatic monomer units and a block mainly composed of vinyl aromatic monomer units.

[0047] The copolymer block mainly containing a conjugated diene monomer unit and also containing a vinyl aromatic monomer unit is not particularly limited, and the above-mentioned conjugated diene monomer and vinyl aromatic monomer can be used. Among them, from the viewpoint of the balance between mechanical strength and impact resistance, preferred combinations include a block containing a butadiene unit and a styrene unit, a block containing an isoprene unit and a styrene unit, etc.

[0048] In the copolymer block mainly containing conjugated diene monomer units and also containing vinyl aromatic monomer units, the content of each monomer is not particularly limited as long as it mainly contains at least conjugated diene monomer units. In particular, from the viewpoint of the balance between mechanical strength and impact resistance, the content of vinyl aromatic monomer units in the copolymer block is preferably 10% by mass or more and less than 50% by mass, more preferably 20% by mass or more and less than 50% by mass.

[0049] From the viewpoints of moldability and scratch resistance, the content of component (C) in the composition of the present invention is 30 to 250 parts by mass, preferably 35 to 220 parts by mass, more preferably 40 to 180 parts by mass, and even more preferably 45 to 150 parts by mass, per 100 parts by mass of component (A).

[0050] <Softener (D)> The softener (D) is not particularly limited, but is preferably a process oil composed of a paraffinic, naphthenic, aromatic or other hydrocarbon. Among these, a process oil mainly composed of a paraffinic hydrocarbon or, from the viewpoint of compatibility with rubber, mainly composed of a naphthenic hydrocarbon is preferred. From the viewpoint of thermal and light stability, the content of aromatic hydrocarbons in the process oil is preferably 10% or less, more preferably 5% or less, and even more preferably 1% or less, in terms of carbon number ratio according to the ASTM D2140-97 standard.

[0051] The content of component (D) in the composition of the present invention is 100 to 300 parts by mass, preferably 100 to 280 parts by mass, more preferably 100 to 250 parts by mass, and even more preferably 100 to 220 parts by mass, relative to 100 parts by mass of component (A) from the viewpoint of adjusting the hardness and flexibility of the composition. By setting the content of component (D) within the above range, flexibility and processability can be further improved, and bleeding of component (D) can be further suppressed.

[0052] <Polyorganosiloxane (E)> The structure of the polyorganosiloxane (E) is not particularly limited, but from the viewpoint of abrasion resistance and touch, it is preferable that the polyorganosiloxane (E) has a crosslinked polymer structure such as a linear or branched structure, and has a kinematic viscosity (25°C) of 5000 centistokes (cSt) or more according to the JIS-K2410 standard. Useful polyorganosiloxanes are generally polymers containing siloxane units substituted with alkyl groups, vinyl groups, and / or aryl groups, and polydimethylsiloxanes substituted with methyl groups are more preferable.

[0053] The content of component (E) in the composition of the present invention is 1 to 30 parts by mass, preferably 1 to 25 parts by mass, more preferably 3 to 25 parts by mass, and even more preferably 5 to 20 parts by mass, relative to 100 parts by mass of component (A). By setting the content of component (E) within the above range, it is possible to improve the wear resistance and further suppress the bleeding of component (E).

[0054] <Organic peroxide (F)> The thermoplastic elastomer composition of the present invention is at least partially crosslinked. As described above, it is preferable that at least a part of the component (B) is crosslinked. This allows the crosslinked body to incorporate the softener and suppress the volatilization of the softener, thereby improving the flame retardancy and allowing a large amount of the softener to be contained, thereby obtaining a composition with excellent moldability. The method of crosslinking is not particularly limited, but it is preferable to crosslink using a crosslinking agent such as an organic peroxide (F).

[0055] The amount of organic peroxide (F) used is not particularly limited, but is preferably 0.1 to 10 parts by mass, more preferably 1 to 10 parts by mass, even more preferably 2 to 8 parts by mass, and particularly preferably 2 to 5 parts by mass, relative to 100 parts by mass of component (A).

[0056] Specific examples of the organic peroxide (F) include 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, 1,1-bis(t-butylperoxy)cyclododecane, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(t-butylperoxy)octane, n-butyl-4,4-bis(t-butylperoxy)butane, n-butyl-4,4-bis(t peroxyketals such as di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, α,α'-bis(t-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane and 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3; acetyl peroxide, isobutyryl peroxide, diacyl peroxides such as octanoyl peroxide, decanoyl peroxide, lauroyl peroxide, 3,5,5-trimethylhexanoyl peroxide, benzoyl peroxide, 2,4-dichlorobenzoyl peroxide and m-trioyl peroxide; t-butyl peroxyacetate, t-butyl peroxyisobutyrate, t-butyl peroxy-2-ethylhexanoate, t-butyl peroxylaurate, t-butyl peroxybenzoate, di-t-butyl peroxy Examples of the peroxyesters include isophthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butylperoxymaleic acid, t-butylperoxyisopropyl carbonate, and cumylperoxyoctate; and hydroperoxides such as t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, and 1,1,3,3-tetramethylbutyl peroxide.

[0057] Among these compounds, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, di-t-butyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane and 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3 are preferred.

[0058] Crosslinking using the organic peroxide (F) can be carried out by a known method. If necessary, a polyfunctional monomer or a monofunctional monomer may be used as a crosslinking aid. The polyfunctional monomer as the crosslinking aid preferably has a radical polymerizable functional group as a functional group, more preferably a vinyl group. The number of functional groups may be 2 or more, and in combination with the monofunctional monomer, it is particularly effective to have 3 or more functional groups.

[0059] Preferred specific examples of the polyfunctional monomer include divinylbenzene, triallyl isocyanurate, triallyl cyanurate, diacetone diacrylamide, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, diethylene glycol dimethacrylate, diisopropenylbenzene, p-quinone dioxime, p,p'-dibenzoylquinone dioxime, phenylmaleimide, allyl methacrylate, N,N'-m-phenylene bismaleimide, diallyl phthalate, tetraallyloxyethane, and 1,2-polybutadiene. Among these, divinylbenzene and triallyl isocyanurate are more preferred. These polyfunctional monomers may be used alone or in combination of two or more.

[0060] The monofunctional monomer as the crosslinking aid is preferably a radically polymerizable vinyl monomer. This allows the crosslinking reaction rate to be controlled. Examples of the vinyl monomer include aromatic vinyl monomers, unsaturated nitrile monomers such as acrylonitrile and methacrylonitrile, acrylic acid ester monomers, methacrylic acid ester monomers, acrylic acid monomers, methacrylic acid monomers, maleic anhydride monomers, and N-substituted maleimide monomers.

[0061] <Ethylene-α-olefin copolymer (G)> Component (G) is an ethylene-α-olefin copolymer containing ethylene units and α-olefin units having 3 to 20 carbon atoms. Component (G) can be obtained by copolymerizing at least ethylene and an α-olefin having 3 to 20 carbon atoms. Examples of α-olefins having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, and 1-dodecene. Among these, from the viewpoint of imparting flexibility, α-olefins having 3 to 12 carbon atoms are preferred, and propylene, 1-butene, and 1-octene are more preferred.

[0062] It is preferable to use a metallocene catalyst for producing component (G). In general, a metallocene catalyst is composed of a cyclopentadienyl derivative of a Group IV metal such as titanium or zirconium and a cocatalyst. There is no particular limitation on the metallocene catalyst, and any known catalyst can be used. Metallocene catalysts are not only highly active as polymerization catalysts, but also narrow the molecular weight distribution of the resulting copolymer compared to Ziegler catalysts, and can uniformly distribute the α-olefin having 3 to 20 carbon atoms, which is a comonomer in the copolymer.

[0063] The copolymerization ratio of the α-olefin in component (G) is not particularly limited, but is preferably 1 to 60 mass%, more preferably 10 to 55 mass%, and even more preferably 20 to 50 mass%. By setting the copolymerization ratio of the α-olefin within the above range, the mechanical strength (tensile strength, etc.) and flexibility of the thermoplastic elastomer composition can be further improved.

[0064] The density of component (G) is not particularly limited, but is preferably 0.8 to 0.9 g / cm 3 By using component (G) having a density in this range, a thermoplastic elastomer composition having even more excellent flexibility can be obtained.

[0065] The structure of component (G) is not particularly limited, but it is preferable that it has a long chain branch. Here, the long chain branch refers to a branch having 3 or more carbon atoms. By having a long chain branch, it is possible to reduce the density compared to the copolymerization ratio (mass%) of the copolymerized α-olefin without reducing the mechanical strength. As a result, a thermoplastic elastomer composition with a lower density and higher strength can be obtained.

[0066] Component (G) preferably has a melting point peak in differential scanning calorimetry (DSC) in a temperature range above room temperature. By having component (G) have a melting point peak in a temperature range above room temperature, it is possible to obtain a thermoplastic elastomer that has excellent shape stability in a temperature range below the melting point, excellent handleability, and little stickiness.

[0067] The melt flow rate of component (G) is preferably in the range of 0.1 to 100 g / 10 min (190° C., 2.16 kg load (0.212 Pa), in accordance with ASTM D1238), and more preferably in the range of 0.2 to 20 g / 10 min. By setting the melt flow rate within the above range, a thermoplastic elastomer with a better balance between fluidity and mechanical strength can be obtained.

[0068] From the viewpoint of a balance between moldability and flexibility, the content of component (G) in the composition of the present invention is preferably in the range of more than 0 parts by mass and not more than 300 parts by mass, more preferably more than 0 parts by mass and not more than 250 parts by mass, even more preferably more than 0 parts by mass and not more than 150 parts by mass, and particularly preferably more than 0 parts by mass and not more than 120 parts by mass, per 100 parts by mass of component (A).

[0069] <Other ingredients> The composition of the present invention may contain inorganic fillers and plasticizers as components other than the above-mentioned components (A) to (G) within the scope of not impairing the effects of the present invention. Examples of inorganic fillers used here include calcium carbonate, magnesium carbonate, silica, carbon black, glass fiber, titanium oxide, clay, mica, talc, magnesium hydroxide, and aluminum hydroxide. Examples of plasticizers include polyethylene glycol and phthalate esters such as dioctyl phthalate (DOP). In addition, other additives such as organic and inorganic pigments, heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, silicone oils, antiblocking agents, foaming agents, antistatic agents, and antibacterial agents may also be contained in the thermoplastic elastomer composition.

[0070] Furthermore, the composition of the present invention may contain a flame retardant, but it is preferable that the content is low or substantially free of the flame retardant from the viewpoints of moldability, cost, etc. Specifically, when the entire composition is taken as 100% by mass, the content of the flame retardant is preferably less than 10% by mass, more preferably 5% by mass or less, even more preferably 1% by mass or less, and particularly preferably less than 0.1% by mass.

[0071] <Method of producing thermoplastic elastomer composition> For the production of the thermoplastic elastomer composition of the present invention, general methods such as a Banbury mixer, a kneader, a single screw extruder, and a twin screw extruder, which are used for the production of ordinary resin compositions and elastomer compositions, can be adopted. Among these, a twin screw extruder is preferable from the viewpoint of achieving dynamic crosslinking efficiently. A twin screw extruder can not only uniformly and finely disperse the components (A) to (F), but also promote the crosslinking reaction by adding other components. As a result, it is preferable because the thermoplastic elastomer composition can be continuously produced.

[0072] The thermoplastic elastomer composition of the present embodiment is preferably produced via the following processing steps. Components (A) to (C) and, if necessary, component (G) are thoroughly mixed and charged into the hopper of the extruder. The timing of adding the crosslinking agent such as the organic peroxide (F) is not limited, and for example, it may be added from the beginning together with components (A) to (C), or a part of the crosslinking agent may be added midway through the extruder. Furthermore, a part of components (A) to (C) may be added midway through the extruder.

[0073] The timing of adding the softener (D) is not limited, and for example, it may be added from the middle of the extruder, or may be added separately at the beginning and the middle. Even in this case, if necessary, a part of the crosslinking agent may be added from the middle of the extruder. Furthermore, it is also possible to mix the additive and the softener in advance and add it.

[0074] The timing of adding the polyorganosiloxane (E) is not limited, and it may be added from the beginning, or may be added in portions at the beginning and during the process, or may be added during the process. The method of adding the component (E) is not particularly limited, and it may be a method of adding a master batch containing a high concentration of polyorganosiloxane in advance using any thermoplastic resin or elastomer.

[0075] When heated, melted and kneaded in the extruder, component (B) and the crosslinking agent undergo a crosslinking reaction, and at the same time, component (A) undergoes a decomposition reaction with the crosslinking agent, which can improve molding flowability. Furthermore, by adding a softener (D) and melt-kneading the mixture, the crosslinking reaction and kneading dispersion are sufficiently performed, and then the mixture is taken out of the extruder, pellets of the thermoplastic elastomer composition of the present embodiment can be obtained.

[0076] A particularly preferred melt extrusion method is a method using a twin-screw extruder having a length L from the raw material addition section in the die direction and an L / D ratio in the range of 5 to 100 (where D represents the barrel diameter). The twin-screw extruder preferably has a plurality of feed sections, including a main feed section and a side feed section, which are at different distances from the tip of the extruder. The twin-screw extruder also preferably has kneading sections between the plurality of feed sections and between the tip and a feed section close to the tip, and the length of each of these kneading sections is preferably 3D to 10D.

[0077] The twin-screw extruder, which is one of the manufacturing devices that can be used in this embodiment, may be a twin-screw co-rotating extruder or a twin-screw counter-rotating extruder. Regarding the intermeshing of the screws, any type may be used, including non-intermeshing, partial intermeshing, and complete intermeshing. When a low shear force is applied to obtain a uniform resin at a low temperature, a counter-rotating, partial intermeshing screw is preferred. When a slightly larger amount of kneading is required, a co-rotating, complete intermeshing screw is preferred. When even larger amount of kneading is required, a co-rotating, complete intermeshing screw is preferred.

[0078] From the viewpoint of imparting excellent mechanical strength to the resulting thermoplastic elastomer composition, it is more preferable that the degree of kneading M when kneading using a twin-screw extruder satisfies the relationship of the following formula (i).

[0079] 10×10 6 ≦M≦1000×10 6 (i) Here, the degree of kneading M: (π 2 / 2)(L / D)D 3 (N / Q), L: extruder length from the raw material addition point toward the die (mm), D: Extruder barrel inner diameter (mm), Q: Discharge amount (kg / h), N: screw rotation speed (rpm).

[0080] In formula (i), the degree of kneading M is 10 × 10 6 By setting the M at 1000×10 or more, it is possible to prevent the rubber particles from becoming enlarged or agglomerated, and to obtain a good appearance. 6 By setting the value of the shear strength to be equal to or less than 100%, it is possible to prevent a decrease in mechanical strength due to an excessive shear force.

[0081] <Characteristics of Thermoplastic Elastomer Composition> The composition of the present invention obtained as described above has a surface hardness (Shore A hardness, 10 second value) measured in accordance with JIS K7215 of preferably 40 to 80, more preferably 45 to 78, even more preferably 50 to 75, and particularly preferably 55 to 75.

[0082] Furthermore, the burning rate in a burning test in accordance with FMVSS No. 302 using a test piece (thickness: 1.2 mm) made of the composition of the present invention is preferably 85 mm / min or less, more preferably 80 mm / min or less, even more preferably 75 mm / min or less, particularly preferably 70 mm / min or less, and most preferably 60 mm / min or less.

[0083] [Application] The above-mentioned composition of the present invention can be molded by a known molding method to obtain various molded articles. Examples of the molding method include injection molding, extrusion molding, vacuum molding, pressure molding, blow molding, calendar molding, and foam molding. For example, the composition of the present invention that has been heated and melted can be filled into a mold for molding, cooled and solidified, and then demolded to obtain a molded article such as a skin material.

[0084] The composition of the present invention is preferably formed into an injection molded article because of its excellent productivity. The shape of the injection molded article is not particularly limited, but is preferably a film or sheet from the viewpoint of use as a skin material.

[0085] The injection molded article can be used for various components, but is preferably used as an interior material for automobiles, in particular from the viewpoint that thin-walled molded articles having complex shapes can be injection molded with good reproducibility.

[0086] By using the composition of the present invention, it is possible to efficiently manufacture thin-walled components with a large surface area and complex shape, which have been difficult to manufacture by injection molding in the past. For example, in the case of automobile interior materials, the average thickness is 2 mm or less and the surface area is 1000 cm. 2 It is possible to realize an automobile interior material having the above average thickness and surface area. Conventionally, it has been difficult to produce an automobile interior material having such an average thickness and surface area by injection molding. However, by using the composition of the present invention, even such an automobile interior material can be produced by injection molding with good productivity.

[0087] Furthermore, among automotive interior materials, instrument panels are not only thin and have a large surface area, but also usually have a complex shape with a grain pattern on the surface, some openings, curved surfaces as well as flat surfaces, three-dimensional structures, and thick surfaces as well as thin surfaces. According to the present invention, an injection molded article having a thin wall and a large surface area can be obtained, and is therefore suitable for use as an instrument panel or a component thereof. Specifically, a molded article for use as such an instrument panel or a component thereof has an average thickness of 2 mm or less and a surface area of ​​1000 cm2. 2 As described above, it has been difficult to produce such a molded article by injection molding in the past, but the present invention makes it possible to produce such a molded article by injection molding.

[0088] The shape and configuration of the automotive interior material are not particularly limited, and may be appropriately selected according to the application. A preferred example is a laminate including a layer (hereinafter also referred to as a "skin layer") containing the automotive interior material of this embodiment, and a layer (hereinafter also referred to as a "core layer") containing a core material that is laminated on the layer containing the automotive interior material. By forming a laminate that includes not only a skin layer but also a core layer, even a complex three-dimensional shape can be mass-produced stably, thereby improving production efficiency and reducing costs.

[0089] The material of the core material is not particularly limited, and known materials can be used, such as polypropylene, acrylonitrile butadiene styrene (ABS) resin, polycarbonate / acrylonitrile butadiene styrene alloy (PC / ABS alloy), acrylonitrile styrene copolymer, modified polyphenylene oxide, and resins in which fillers such as talc and glass fiber are mixed as necessary to improve strength. Among these, those containing at least one selected from the group consisting of polypropylene, acrylonitrile butadiene styrene (ABS) resin, polycarbonate / acrylonitrile butadiene styrene alloy (PC / ABS alloy), and polyphenylene ether are preferred. Furthermore, polypropylene is more preferred from the viewpoint of light weight.

[0090] The layer structure of the laminate of this embodiment is not particularly limited, and may be a two-layer or more structure having at least a skin layer and a core layer. In this embodiment, the skin layer and the core layer do not necessarily need to be in contact with each other, and another layer may be present between the skin layer and the core layer.

[0091] The thickness of the skin layer is not particularly limited, but is preferably 0.5 to 2.0 mm, and more preferably 0.8 to 1.5 mm. By making the thickness of the skin layer 0.5 mm or more, it is possible to improve the appearance, chemical resistance, and abrasion resistance, and by making the thickness 2.0 mm or less, it is possible to improve the economy and the touch. It has been difficult to efficiently produce such a thin skin layer with conventional techniques, but by using the composition of the present invention, it is possible to easily produce such a thin skin layer.

[0092] The thickness of the core layer is not particularly limited, but is preferably 2.0 to 4.5 mm, and more preferably 2.5 to 3.5 mm. By making the thickness of the core layer 2.0 mm or more, the rigidity, heat resistance, and moldability can be further improved, and by making the thickness 4.5 mm or less, the economy and lightness can be further improved.

[0093] Furthermore, the laminate of the present embodiment preferably further comprises a layer containing a foam material between the skin layer and the core layer, and the foam material has a density of 100 to 250 kg / m 3 It is more preferable that the foam contains a thermosetting urethane foam having a density of 100 kg / m 3 By setting the density of the foam material at 250 kg / m or more, it is difficult for the foam material to be indented during handling during production or removal, and handling properties can be further improved. 3 By setting the density of the foam material to 120 to 180 kg / m or less, it is possible to impart appropriate flexibility to the laminate. 3 It is more preferable that:

[0094] The type of thermosetting urethane foam is not particularly limited, but it is preferably a semi-rigid thermosetting urethane foam, which means a urethane foam having an open cell structure of 90% or more.

[0095] The method for producing the laminate is not particularly limited, and known methods can be adopted. For example, a method in which the skin material, the core material, and the foam material are molded separately, and then the above members are laminated using a chloroprene-based adhesive to form a layer structure, or a method in which the core material is molded in advance, the core material is placed in a mold, and molded integrally with the molding of the skin material (integral molding), and the core material and the two members are laminated to form a layer structure can be mentioned.

[0096] By using the above layer structure, it is possible to obtain a laminate having a uniform thickness, good grain reproducibility, and a skin material with good texture and appearance, and capable of stable mass production even in three-dimensional complex shapes. Furthermore, by using a layer structure of three or more layers including the above foam material, it is possible to obtain a laminate that further utilizes the soft texture of the skin material.

[0097] The laminate can be suitably used as automotive interior components, such as thin-walled instrument panels, door panels, glove box lids, and the like, which have traditionally been difficult to produce by injection molding, and is particularly suitable as instrument panels. EXAMPLES

[0098] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way. [Evaluation method] The evaluation methods for each component used in the examples and comparative examples are as follows.

[0099] <Hydrogenation rate (%)> The hydrogenation rate was measured by nuclear magnetic resonance spectroscopy (NMR). A nuclear magnetic resonance measuring device (manufactured by JEOL, device name "JNM-LA400") was used as the measuring device, deuterated chloroform was used as the solvent, and tetramethylsilane (TMS) was used as the chemical shift standard. The measurement was performed under the conditions of a sample concentration of 50 mg / mL, an observation frequency of 400 MHz, a pulse delay of 2.904 seconds, a scan count of 64 times, a pulse width of 45°, and a measurement temperature of 26°C.

[0100] <Content of monomer units and bond units> The contents of ethylene monomer units, α-olefin monomer units, non-conjugated diene monomer units, vinyl aromatic monomer units, butylene monomer units, butadiene 1,4-bond units, 1,2-bond units and 3,4-bond units were measured by NMR. A nuclear magnetic resonance measurement device (manufactured by JEOL, device name "JNM-LA400") was used as the measurement device, deuterated chloroform was used as the solvent, and tetramethylsilane (TMS) was used as the chemical shift standard. The measurement was performed under the conditions of a sample concentration of 50 mg / mL, an observation frequency of 400 MHz, a pulse delay of 2.904 seconds, a scan count of 64 times, a pulse width of 45° and a measurement temperature of 26°C.

[0101] The mass fraction (mass%) of each structural unit contained in the ethylene-α-olefin copolymer (G) is 13 Specifically, the measurement was performed using an ECX400P nuclear magnetic resonance spectrometer (manufactured by JEOL Ltd.) under the following conditions: measurement temperature: 120° C., measurement solvent: orthodichlorobenzene / deuterated benzene=4 / 1 (volume ratio), and number of accumulations: 8000. 13 Calculated from the C-NMR spectrum.

[0102] <Styrene polymer block content (Os value)> The styrene polymer block content was measured by the method (osmium tetroxide decomposition method) described in IM Kolthoff, et al., J. Polym. Sci. 1, 429 (1946) using the copolymer before hydrogenation. A 0.1 g / 125 mL tertiary butanol solution of osmic acid was used to decompose the copolymer before hydrogenation. The styrene polymer block content was calculated by the following formula. The styrene polymer block content obtained here is called the "Os value." It is called. Styrene polymer block content (Os value; mass%)=(mass of styrene polymer block in copolymer before hydrogenation) / mass of copolymer before hydrogenation)×100

[0103] <Peak temperature of loss tangent (tan δ)> The viscoelasticity was determined by measuring the viscoelasticity spectrum using a viscoelasticity measurement analyzer (ARES, manufactured by Ta Instruments) under conditions of strain of 0.1% and frequency of 1 Hz.

[0104] [material] The components of the resin compositions produced in the examples and comparative examples are as follows. (A) Propylene-based polymer Homopolypropylene (product name: Sunallomer (registered trademark) PL400A; manufactured by Sunallomer; melt flow rate (MFR) at 230° C. and a load of 2.16 kg: 2.0 g / 10 min) was used.

[0105] (B) Ethylene-α-olefin-non-conjugated polyene copolymer (EPDM) A copolymer of ethylene, propylene and 5-ethylidene-2-norbornene (ENB) was used, in which the ethylene content was 70 mass % and the ENB content was 4.9 mass %.

[0106] (C) Hydrogenated block copolymer <Method for producing block copolymer (C-1)> (1) Preparation of hydrogenation catalyst The hydrogenation catalyst used in the hydrogenation reaction of the block copolymer was prepared by the following method: 1 L of dried and purified cyclohexane was charged into a nitrogen-substituted reaction vessel, 100 mmol of bis(cyclopentadienyl)titanium dichloride was added, and an n-hexane solution containing 200 mmol of trimethylaluminum was added while thoroughly stirring, and the reaction was carried out at room temperature for about 3 days.

[0107] (2) Production of hydrogenated block copolymers Batch polymerization was carried out using a tank reactor with a jacket and a stirring device with an internal volume of 10 L. First, 6.4 L of cyclohexane and 75 g of styrene were added, and TMEDA was added in advance so that the number of moles of Li in n-butyllithium was 0.25 times the molar number of n-butyllithium. The number of moles of Li in the n-butyllithium initiator was 10 mmol. Polymerization was carried out at an initial temperature of 65° C. After the polymerization was completed, a cyclohexane solution containing 470 g of butadiene and 380 g of styrene (monomer concentration 22% by mass) was continuously fed to the reactor at a constant rate over 60 minutes. After polymerization, a cyclohexane solution containing 75 g of styrene (monomer concentration 22% by mass) was added over 10 minutes to obtain a copolymer. The styrene content in the obtained copolymer was 53% by mass, the styrene polymer block content in the copolymer was 15% by mass, the styrene content in the copolymer block (i.e., the copolymer block containing a conjugated diene monomer unit and a vinyl aromatic monomer unit) was 45% by mass, and the vinyl bond content in the copolymer was 23%.

[0108] The hydrogenation catalyst was added to the obtained copolymer at 100 ppm titanium per 100 parts by mass of the polymer, and hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 75°C. 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added to the obtained polymer solution as a stabilizer per 100 parts by mass of the hydrogenated block copolymer. The weight average molecular weight of the obtained hydrogenated block copolymer (C-1) was 160,000, and the hydrogenation rate of the butadiene double bonds contained in the hydrogenated block copolymer (C-1) was 99%. In addition, one of the tan δ peaks obtained by viscoelasticity measurement was present at -15°C.

[0109] <Method for producing block copolymer (C-2)> Batch polymerization was carried out using a tank reactor with a jacket and a stirring device with an internal volume of 10 L. First, 6.4 L of dried and purified cyclohexane and 175 g of styrene were added, and tetramethylethylenediamine (TMEDA) was added in advance so that the molar amount was 0.30 times the number of moles of Li in the n-butyllithium initiator, and the number of moles of Li in the n-butyllithium initiator was 11 mmol. Then, polymerization was carried out at an initial temperature of 65° C., and after the polymerization was completed, a cyclohexane solution containing 650 g of butadiene (monomer concentration 22% by mass) was continuously fed to the reactor at a constant rate over 60 minutes, and then a cyclohexane solution containing 175 g of styrene (monomer concentration 22% by mass) was further added over 10 minutes to obtain a copolymer. The styrene polymer block content in the obtained copolymer was 35% by mass, and the vinyl bond content was 36%.

[0110] The hydrogenation catalyst was added to the copolymer obtained so that the amount was 100 ppm in terms of titanium per 100 parts by mass of the copolymer, and hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 75°C to obtain a reaction solution. Octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer to the reaction solution obtained in an amount of 0.3 parts by mass per 100 parts by mass of the hydrogenated block copolymer. The weight average molecular weight of the hydrogenated block copolymer obtained (C-2) was 150,000, and the hydrogenation rate of the double bonds of butadiene contained in the hydrogenated block copolymer (C-2) was 99%.

[0111] (D) Softener Paraffin-based oil (manufactured by Idemitsu Kosan Co., Ltd., product name "Diana Process Oil PW-100") was used.

[0112] (E) Polyorganosiloxane Dimethylsiloxane with a kinematic viscosity of 60,000 cSt at 25° C. was used.

[0113] (F) Crosslinking agent The crosslinking agent used was a crosslinking initiator containing 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane (manufactured by Nippon Oil & Fats Corporation, product name "Perhexa 25B") and the following amount of the following crosslinking aid (polyfunctional monomer) per 100 parts by mass of 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane. Divinylbenzene (manufactured by Wako Pure Chemical Industries, Ltd.; hereinafter referred to as "DVB") 15 parts by mass

[0114] (G) Ethylene-α-olefin copolymer A copolymer of ethylene and 1-octene (trade name "Engage 8842" manufactured by Dow Chemical Company) was used. The ethylene content of this copolymer was 55% by mass, and the 1-octene content was 45% by mass.

[0115] Flame retardants The halogen-free flame retardant used was ADEKA Corporation's product name "FP-2500S."

[0116] [Examples and Comparative Examples] <Production of Composition> The extruder used was a twin-screw extruder (30 mmφ, L / D=74; Kobe Steel, "KTX-30") with an oil inlet in the center of the barrel. A two-thread screw with kneading sections before and after the inlet was used as the screw. The raw materials other than the softener (D) were mixed together in the composition ratio (parts by mass ratio) shown in Table 1, and then introduced into the twin-screw extruder (cylinder temperature 200°C) with a fixed quantity feeder. Subsequently, the softener (D) in the amount shown in Table 1 was pumped into the inlet in the center of the extruder, and melt extrusion was performed to obtain a thermoplastic elastomer composition.

[0117] <Press sheet molding> The thermoplastic elastomer composition obtained above was compression molded at 200° C. using a hot press machine (manufactured by Toho Press Manufacturing Co., Ltd., “T-50”) to produce a sheet with a thickness of 2 mm.

[0118] <Injection molding> The thermoplastic elastomer composition was injection molded using a flat plate mold measuring 350 mm in length, 100 mm in width, and 1.2 mm in thickness to obtain an injection molded product. The injection molding machine used was the "M150CL-DM" manufactured by Meiki Seisakusho Co., Ltd. The molding conditions were a resin temperature of 220°C and a mold temperature of 40°C.

[0119] <Evaluation> The physical properties of the obtained thermoplastic elastomer compositions and samples were evaluated by the following methods. The results are shown in Table 1.

[0120] (1) Shore A hardness measurement In accordance with JIS K6253, a laminated sheet having a thickness of 6 mm obtained by stacking three sheets each having a thickness of 2 mm obtained above was measured using a Shore A hardness tester, and the value read 10 seconds after the pressure plate was brought into contact with the test piece was determined as the Shore A hardness (10 second value).

[0121] (2) Burning speed In accordance with FMVSS No. 302, the burning rate (mm / min) was measured using the injection molded article having a thickness of 1.2 mm obtained above.

[0122] [Table 1]

Claims

1. 100 parts by mass of propylene polymer (A), 10 to 300 parts by mass of an ethylene / α-olefin / non-conjugated polyene copolymer (B), 30 to 250 parts by mass of a hydrogenated block copolymer (C) having a block mainly composed of conjugated diene monomer units and a block mainly composed of vinyl aromatic monomer units, A softener (D) of 100 to 300 parts by mass, and Polyorganosiloxane (E): 1 to 30 parts by mass Contains the component (C) comprises a hydrogenated product of a block copolymer mainly comprising conjugated diene monomer units and having a copolymer block containing vinyl aromatic monomer units and a block mainly comprising vinyl aromatic monomer units, An at least partially crosslinked thermoplastic elastomer composition.

2. The thermoplastic elastomer composition according to claim 1 , wherein the crosslinking is caused by an organic peroxide (F).

3. The thermoplastic elastomer composition according to any one of claims 1 to 2, further comprising an ethylene / α-olefin copolymer (G) in an amount of more than 0 part by mass and not more than 300 parts by mass.

4. The thermoplastic elastomer composition according to any one of claims 1 to 3, wherein at least a portion of said component (B) is crosslinked.

5. The thermoplastic elastomer composition according to any one of claims 1 to 4, which has a surface hardness (Shore A hardness, 10 second value) of 40 to 80 as measured in accordance with JIS K7215.

6. The thermoplastic elastomer composition according to any one of claims 1 to 5, which has a burning rate of 85 mm / min or less in a burning test (test piece thickness: 1.2 mm) according to FMVSS No.

302.

7. An injection molded article comprising the thermoplastic elastomer composition according to any one of claims 1 to 6.

8. A film or sheet comprising the injection molded article according to claim 7.

9. An automobile interior material comprising the injection molded article according to claim 7.

Citation Information

Patent Citations

  • Thermoplastic elastomer composition

    JP1996319383A

  • Hydrogenated diene-based copolymer and method for producing the same

    JP2005255856A

  • Thermoplastic elastomer composition having soft touch feeling and molded article thereof

    JP2019001888A

  • Thermoplastic elastomer composition and molded articles thereof

    WO2011155571A1

  • Display device

    WO2021054271A1